Conformational Studies of ε- CBz- L- Lysine and L- Valine Block Copolypeptides - Ajay Kumar (E-Journal of Chemistry)
Conformational studies of ε-CBz-L-lysine and L-valine block copoylpeptides using x- ray diffraction and CD spectra are described. The block copolypeptides contain valine block in the center and on both side of the valine are ε-CBz-L-lysine blocks. The conformation of the copolypeptides changes with increases in the chain length of ε- CBz-L- lysine blocks. When length of ε- CBZ- L- lysine blocks is 9, the block copolypeptide has exclusive beta sheet structure. With the increase in chain length of ε-CBz-L-lysine blocks from 9 to 14, the block copolypeptide shows presence of both alpha helix and beta sheet components. With further increase in chain length of ε- CBz- L- lysine blocks, the beta sheet component disappears and block copolypeptides exhibits exclusive α -helix conformation.